Research and creation of working organs of the tomato seed separator device - V. P. Gorobey; V. Y. Moskalevich; V. F. Pivovarov; L. V. Pavlov (Овощи России, 2022)
Relevance. Seeds play an important role in obtaining a high yield of vegetable crops of good quality. Breeders usually deal with a large number of samples. To study the source material, the seeds of the samples are sown in boxes with soil for growing seedlings or in collection nurseries of experimental stations and research institutions. It takes an average of ½ hour of shift time to manually extract a sample weighing 10 kg from a batch. Currently, there are no sufficiently efficient devices for isolating tomato seeds from batches of samples with small weights up to 100 kg. The task of research on mechanization is to increase the efficiency of the tomato seed extraction device by improving the working bodies, determining the value of the optimal mass of samples, the extraction of seeds from which is economically and technically feasible.Material and methodology. Experimental studies were conducted in order to find constructive solutions for working bodies, study their operability and determine optimal parameters and operating modes. The research program included: a study of the productivity of the layout and the complexity of its maintenance; a study of qualitative indicators, including seed loss, seed clogging, seed damage; a study of the modes of working bodies, including the number of revolutions of the whip shaft, gaps between the whips and the sieve, the angle of advance of the whips; an assessment of the convenience of cleaning and visual inspection of all surfaces of parts, in contact with seeds; analysis of the advantages and disadvantages of the design of mesh drums, scourges, mechanisms for locking semi-cylinders, the work of the fence that reclines together with the hopper.Results. As a result of the research, it was found that drum-and-whip type working organs are economically feasible for use in tomato seed extraction devices with a sample weight of at least 100 kg (i.e. mainly in primary and elite seed production), due to the fact that the time for disassembly, cleaning and assembly of working organs is 95% of the cycle (for example for samples weighing 10 kg). The clogging of the seeds meets the requirements, crushing was not observed.